3D technology for mobile robot - Nguyen, Quang Ngoc. (2009)
This project focuses on details of objects detection and localization programs using OpenCV for an autonomous robot. In addition, the speech system is integrated into the robot system so that the robot can inform its operations and planning progress by launching voice, which is a good way to monitor robot’s states and make rooms for further developments. A text-to-speech (TTS) system converts normal language text into speech to provide the robot such ability. Moreover, a method for pattern recognition using the Viola and Jones classifier built in to OpenCV is also discussed. This method is used to detect street scenery, which is one of the fundamental parts for line and curve detection in traffic control.